Enhancing Environmental Literacy in Aceh’s Tourism through an Ethnoecotourism Based Environmental Education Model - Aswita, Dian; Noviyanti, Anita; Apriana, Evi; Jalaluddin, Jalaluddin; Febriyanti, Dewi; Herlina, Herlina; Hasmita, Ida (Jurnal Ilmiah Peuradeun, 2024)
Trends in tourism motives include socio-cultural, customs, environment, and panorama, as well as economics and welfare. However, the implementation of tourism will undoubtedly be disrupted by management and development that are not founded on the principles of sustainability. Therefore, through the process of environmental education, preventative and awareness initiatives are required. The main objective of this research was to examine the effectiveness of an ethnoecotourism-based environmental education model for tourism actors in Aceh Province. This model was developed to increase environmental literacy in marine tourism management. Model trials were carried out in the Sabang City Marine Tourism Area. The participants of this research were tourism actors in Aceh Province. The research design uses a quasi-experimental method consisting of pretest-posttest groups and uses multiple-choice questions as a research tool. The data analysis technique applied in this research was quantitative descriptive analysis techniques, in which data were processed inductively using an interactive analysis model. It is known that this model could improve the environmental literacy skills of tourism actors at the research location. It was shown by the significant value obtained at p = 0.000 (< 0.05), where there was a difference in students’ scores after being given the learning process, with the average post-test score of 12.43, higher than the pretest score of 8.40, which means there was an increase in understanding of environmental literacy after being given a learning process using an ethnoecotourism-based environmental education model.